Problems Faced in Marketing of Tea Production in Nilegiri Districts- A Micro Study - Kathirvel, N (Journal of Commerce and Trade, 2010)
India’s tea exports data has showed 10% decline in May with a Volume of 9.77m kg owing to increase in the domestic consumption despite the higher prices for the commodity in the domestic market. The industry provides employment to about two million skilled and semi-skilled workers besides those who are employed in ancillary activities, mostly from rural areas. Though the industry contributes a lot to the socio-economic development of the nation, it is plagued with a number of problems such as cyclical fluctuations, high support prices payable to farmers, lack of adequate working capital, partial decontrol and the uncertain export outlook. Despite the problems, the industry has good growth potential due to steady increase in Tea consumption, retail boom and diversification into areas such as power generation and production of ethanol. The main aim of this study is to identify the problems and prospects associated with manufacturing and marketing of Tea in this study area and come out with certain workable solutions to safeguard the interest of the producer –cum seller of Tea.